Anti-inflammatory activity and phenolic composition of a traditional medicinal plant from Turkey: Potentilla recta L. - Okdem, Basak; Karatoprak, Gokce Seker; Kosar, Muberra (Natl Inst Science Communication-Niscair, 2018)
Potentilla recta L. (Rosaceae) is traditionally used for its antibacterial, anti-inflammatory effects and as a tonic in Turkey. In this study, phenolic composition and anti-inflammatory activities of aerial part extract of P. recta from Turkey was examined. The chemical composition was analyzed via spectrophotometric and chromatographic (LC-MS/MS) techniques. The anti-inflammatory activity was determined by measuring the inhibitory effects on nitric oxide (NO) production and determining the levels of tumor necrosis factor alpha (TNF-alpha), interleukin-1 beta (IL-1 beta), interleukin-6 (IL-6) and interleukin-10 (IL-10) in lipopolysaccharide (LPS) stimulated RAW 264.7 cells. P. recta extract decreased the TNF-alpha level significantly compared to LPS group (2045.18 +/- 476.12 pg/mL). Potentillin was identified in the extract and the extract was found to be rich in phenolic compounds. These findings support the traditional use of P. recta with its strong anti-inflammatory activities.
Keywords: Potentilla recta; Potentillin; LC-MS/MS; Anti-inflammatory activity